APPLICATION OF FORENSIC PSYCHOLOGICAL PORTRAITS IN INVESTIGATING SPECIFIC TYPES OF CRIME - Nataliia Аnatolyevna, Zherzh (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2022)
The paper investigates the activities profiled and features of the method of psychological and forensic portrait in the investigation of certain types of crimes. The author carried out a synthesis of available scientific and practical international experience making psychological portraits of unknown criminals, providing recommendations for their practical use in the practice of law enforcement agencies in the investigation of certain categories of offenses, as well as research work Profiler and application of practical experience of foreign countries in the practice of investigative activities in Ukraine